2019
DOI: 10.18632/aging.102469
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal gut microbiota composition contributes to the development of type 2 diabetes mellitus in db/db mice

Abstract: It is well recognized that type 2 diabetes mellitus (T2DM) is an age-related metabolic disease, emerging gradually as a major global health burden that has gained public attention. Meanwhile, increasing attention is paid to the crucial role of gut microbiota in the pathogenesis and therapeutic mechanisms of metabolic disorders, especially T2DM. In this study, we used C57 BL/KS db/db male mice as a T2DM murine model. We found that the β-diversity and relative abundances of gut bacteria were obviously altered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 50 publications
5
42
0
2
Order By: Relevance
“…The authors also reported that other organs, such as liver, lungs, heart, and spleen were smaller [11]. The GF mice in this protocol presented a phenotype consistent with previous publications [13][14][15]. They were lean with no discernable fat, presented a five-fold enlarged cecum relative to controls and exhibited slightly smaller organs; including smaller spleens, lungs, livers, and hearts ( Figure 3A-D).…”
Section: Characterization Of Phenotype (Figure 3)supporting
confidence: 88%
See 1 more Smart Citation
“…The authors also reported that other organs, such as liver, lungs, heart, and spleen were smaller [11]. The GF mice in this protocol presented a phenotype consistent with previous publications [13][14][15]. They were lean with no discernable fat, presented a five-fold enlarged cecum relative to controls and exhibited slightly smaller organs; including smaller spleens, lungs, livers, and hearts ( Figure 3A-D).…”
Section: Characterization Of Phenotype (Figure 3)supporting
confidence: 88%
“…Germ free mice have been extensively used for deciphering some mechanisms linked to diseases, such as Type 2 diabetes mellitus, T2DM [15] behavioral functions at the gut-brain axis and autism [16], cardiovascular diseases [17] and cancer [18]. The use of therapeutics to treat these diseases is also investigated with the use of germ-free colonies and use of a standardized protocol and method would be of interest for future studies.…”
Section: Expected Results and Discussionmentioning
confidence: 99%
“…and lower percentages of order Bacteroidales and family Lachnospiraceae [41]. The β-diversity and relative abundance of intestinal microflora inT2DM mice changes significantly, for example, Bacteroides and Pretium are reduced at the family and genus levels [42]. Evidence shows that the intestinal flora and its metabolites can regulate the hormone secretion function of intestinal endocrine cells, thereby regulating appetite and insulin secretion, which is considered to be the basis of the intestinal flora's effect on many metabolic diseases (e.g., obesity and type II diabetes) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Unbalanced SCFA concentrations in gut lumen can increase intestinal permeability and induce systemic inflammation and insulin resistance due to the synthesis of pro-inflammatory molecules (Poroyko et al, 2016;Feng et al, 2018). Chronic inflammation in obese people promotes clinical progression to metabolic syndrome and some pathologies, such as type 2 diabetes or hepatic steatosis (Ellulu et al, 2015;Kim et al, 2019;Polyzos et al, 2019;Yu et al, 2019). In addition, interactions of the gut-brain axis modulated by microbiota could increase the risk of anxiety, depression, and additional mental disorders (Kelly et al, 2016;Lach et al, 2018).…”
Section: The Gut-brain Axismentioning
confidence: 99%